1979
DOI: 10.1149/1.2129011
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Glucose Oxidation on a Platinized Platinum Electrode in Krebs‐Ringer Solution: II . Potentiostatic Studies

Abstract: The kinetics of the anodic oxidation of glucose in a calcium‐free, Krebs‐Ringer bicarbonate buffer solution at 37°C was studied with a platinized platinum rotating‐disk electrode. Potentiostatic measurements were performed over a potential range of −200 to about 200 mV vs. the saturated calomel electrode (SCE). Excellent reproducibility was achieved by activating the electrode prior to each measurement by an electrochemical pulsing procedure, The current‐time curves did not attain a steady‐state value even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 8 publications
5
33
1
3
Order By: Relevance
“…In polarograms with a mercury dropping electrode^ which permit quantitative measurement of oxidation and reduction processes by characteristic alterations of the current (polarographic steps), we detected no such changes, even at very high glucose concentrations. We must therefore conclude that the glucose-dependent increase of the electrode current as shown by Soeldner et al (14)(15)(16)(17)(18)(19) cannot be explained by a simple redox reaction of glucose at the electrodes.…”
Section: Discussionmentioning
confidence: 84%
“…In polarograms with a mercury dropping electrode^ which permit quantitative measurement of oxidation and reduction processes by characteristic alterations of the current (polarographic steps), we detected no such changes, even at very high glucose concentrations. We must therefore conclude that the glucose-dependent increase of the electrode current as shown by Soeldner et al (14)(15)(16)(17)(18)(19) cannot be explained by a simple redox reaction of glucose at the electrodes.…”
Section: Discussionmentioning
confidence: 84%
“…Gluconolactone undergoes hydrolysis to form gluconic acid [14]. A number of studies showed that gluconic acid can be further oxidized, but at comparably slower reaction rates [15][16][17][18][19]. A detailed treatise on glucose electro-oxidation under different conditions is available elsewhere [20][21][22][23][24][25].…”
Section: Electrode Reactions and Theoretical Potentialsmentioning
confidence: 99%
“…A well-known phenomenon is the gradual deactivation (poisoning) of platinum electrodes when operated for anodic glucose oxidation in neutral buffers. Commonly, this observation is attributed to the adsorption of reaction products and chemisorbed intermediates [18,19]. Generally, there is no agreement in literature regarding the nature of the poisoning species [79].…”
Section: Factors Affecting Long-term Operationmentioning
confidence: 99%
“…Die grundlegenden Untersuchungen zur Glucose-*^^ Messungen an m fr0#oßder$ hohe un4 ten liefert [2,9,13,15,17]. Nach diesen Untersuchungen wurde als Meßpotential für die Glucoseoxidation der Bereich um 400 mV (gegenüber H 2 rev) ausgewählt.…”
Section: Das Meßprinzipunclassified